Theoretical Foundations of the New Industrialization of the Mining Region under Globalization; E3S Web of Conferences; Vol. 15 : International Innovative Mining Symposium (in memory of Prof. Vladimir Pronoza) - Kusurgasheva L. V. Ludmila Vasilyevna (2017, 2017)
Title screen